Les relations sociales, frein ou moteur de la durabilité - Jean-Marc Callois (Développement Durable et Territoires)
Development paths may include contradictions between the different dimensions of sustainability. This article shows the usefulness of the notion of radius of trust in order to evaluate the contribution of social relationships to sustainability. It describes the mechanisms at play, and illustrates the assessment of the radius of trust in six case studies. The higher sustainability turns out to be generally associated with intermediate levels of radius of trust. Such an intermediate level allows to reconcile openness to external resources and stability of the relationships. The article also suggests quantitative measures of the radius of trusts.